Analysis Of The Influence Of Politics, Trust And Instagram Social Media Usage On The Political Habits Of Generation Z In Batam - Eryc Eryc; Calvin Calvin; Indasari Deu (Yayasan Riset dan Pengembangan Intelektual, 2026)
The advancement of digital technology has made Instagram one of the media platforms with significant influence in the process of political communication, particularly among Generation Z. As a cohort born and raised in the digital era, Gen Z is highly engaged with political content through visual displays, interactive features, and internet-based social interactions, which indirectly shape their perspectives and political habits. This study aims to examine how political influence on Instagram, levels of trust, and social media usage contribute to the political habits of Generation Z as young voters in the Riau Islands region, particularly in Batam City. The study employs a quantitative method involving 146 respondents aged 18–25 who are active Instagram users. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach with the SmartPLS 4 application.